Implementing Character Education in Early Childhood: A Case Study of an Islamic Preschool in Indonesia - Salma, Sitti; Ampa, Andi Tendri; Bahri, Aliem (PPSDP International Journal of Education, 2025)
This study aims to investigate the implementation of character education at the Early Childhood Education (PAUD) center Al Manshurin in Kendari City. Employing a qualitative field research methodology, the research observed phenomena within the natural school context. Data were collected through observation, interviews, and documentation involving two key informants: one Group B teacher and the principal. The collected data were analyzed using a qualitative approach encompassing data reduction, data presentation, and conclusion drawing/verification. The results indicate that the implementation, as carried out by the Group B teacher from November to December 2023, was effective. Character education was successfully integrated into daily activities, focusing on cultivating six core noble traits: discipline, honesty, trustworthiness, independence, patience, and mutual respect. The practical implication of this research is that it provides a replicable model for embedding specific character values through consistent routine practices in early childhood settings. The novelty and contribution of this work lie in its focused, empirical examination of a localized Indonesian PAUD context, detailing the operationalization of a distinct set of character values. It contributes to the broader discourse on character education by demonstrating a practical framework for its actualization in early childhood education, offering insights for educators and policymakers aiming to foster moral development from an early age.